Perioperative Means to Prevent Surgical Site Infections following Elective Craniotomies: A Single-Center Experience - Colombo, Francesca; Maye, Helen; Bourama, Eva; Waqar, Mueez; Karabatsou, Konstantina; Coope, David; Bailey, Matthew; Heal, Calvin; Patel, Hiren C.; D'Urso, Pietro I. (Asian Journal of Neurosurgery, 2023)
Background Postoperative surgical site infections are a recognized complication following craniotomies with an associated increase in morbidity and mortality. Several studies have attempted to identify bundles of care to reduce the incidence of infections. Our study aims to clarify which perioperative measures play a role in reducing surgical infection rates further.Methods This study is a retrospective audit of all elective craniotomies in years 2018 to 2019. The primary endpoint was the surgical site infection rate at 30 days and 4 months after the procedure. Univariate analysis was used to identify factors predictive of postoperative infection.Results 344 patients were included in this study. Postoperative infections were observed in 5.2% of our cohort. No postoperative infections occurred within 4 months in patients receiving perioperative hair wash and intrawound vancomycin powder. In univariate analysis, craniotomy size (Fisher's exact test, p = 0.05), lack of perioperative hair wash, and vancomycin powder use (Fisher's exact test, p = 0.01) were predictive of postoperative infection. No complications relative to the use of intrawound vancomycin were observed.Conclusion Our study demonstrates that simple measures such as perioperative hair wash combined with intrawound vancomycin powder in addition to standard practice can help reducing infection rates with negligible risks and acceptable costs. Our results should be validated further in future prospective studies.
Keywords: craniotomy; hair wash; intrawound vancomycin; surgical site infection